Differential Regulation of Wound-Induced 1-Aminocyclopropane-1-Carboxylate Synthase Activity and Gene Expression in Mesocarp Tissue of Winter Squash Fruit by Carbon Dioxide and Diazocyclopentadiene" - Mathooko, Francis; Ono, Tetsu; Kubo, Yasutaka; Inaba, Akitsugu; Nakamura, Reinosuke (Africa Jounals Online, 2001)
Ethylene biosythesis in higher plants induced by various stimuli may be regulated by several factors, among them ethylene action inhibitors. This study investigates the regulation of wound-induced ethylene production, 1-aminocyclopropane-1-carboxylate (ACC) synthase activity and its gene expression and ACC oxidase activity in the mesocarp tissue of winter squash (Cucurbita maxima Duch cv. Ebisu) fruit by elevated CO2 and diazocylopentadiene (DACP), a new inhibitor of ethylene action and/or synthesis. Northern blot nalysis was applied to total RNNA using labeled probes prepared by a multiprimer DNA labeling system and α-[32P]dCTP with a Hindi> III fragment from pCMW33, a wound inducible ACC synthase gene as a template. CO2 suppressed wound-induced ethylene production, ACC synthase and ACC oxidase activities and the expression of ACC synthase gene. The suppression was reversible upon withdrawal of CO2 except that of ACC oxidase activity. The DACP data suggest that wound induced ACC synthase activity and its gene expression, in winter squash fruit are regulated by a negative feedback control mechanism. The CO2 data suggest that CO2 does not regulate wound-induced ACC synthase activity and its gene expression by antagonizing the effects of ethylene produced in response to wounding and may specifically regulate wound-induced ethylene biosynthesis transcriptionally by decreasing ACC synthase mRNA level probably through other yet unknown mechanisms.